INFECTIOUS ARTERIAL ANEURYSM SEBAGAI MANIFESTASI ENDOKARDITIS BAKTERIALIS - Putu Setiani,* Kumara Tini* (NEURONA, 2017)
ARTERIAL ANEURYSM IAA IS A RARE NEUROVASCULAR INFLAMMATORY LESION IAA DEVELOP IN AN INFECTIVE ENDO CARDITIS IE CASES WHEN THE HEARTS FRAGILE VEGETATION CLOGGING A SEPTIC EMBOLIC TO THE INTRACRANIAL BRANCHING VESSELS WE REPORTED A PATIENT DIAGNOSED AS BACTERIAL ENDOCARDITIS AND IAA WITH MAIN COMPLAINT CHRONIC PROGRESSIVE HEADACHE